Prosedur Perpanjangan Sertifikat Nasional Pencegahan Pencemaran dari Kapal Tb Pancaran 118 Pada KSOP Oleh PT. Dean Shipping Agensi Batam - Fober Nainggolan; Yusnidah Yusnidah; Fadiyah Hani Sabila (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
Dean Shipping Agency Batam is a ship agent that handles vessel services at Batam port, from arrival to departure. This research focuses on the process of extending the national pollution prevention certificate, using field observation methods and literature study. The research results show the important role of agents in the process of extending the TB Pancaran 118 vessel certificate. The main constraints include limited experts and non-standardized equipment. Recommendations include improving cooperation, personnel skills, and understanding of agency procedures.